Energy Efficiency : The Innovative Ways for Smart Energy, the Future Towards Modern Utilities - Eissa, Moustafa; Eissa, Moustafa (IntechOpen, 2012)
This book is one of the most comprehensive and up-to-date books written on Energy Efficiency. The readers will learn about different technologies for energy efficiency policies and programs to reduce the amount of energy. The book provides some studies and specific sets of policies and programs that are implemented in order to maximize the potential for energy efficiency improvement. It contains unique insights from scientists with academic and industrial expertise in the field of energy efficiency collected in this multi-disciplinary forum.
English
Keywords: Power generation & distribution; Alternative & renewable energy sources & technology